The use of weight loss products and body mass index among university students in Kota Bharu, Kelantan - Nurul Izzatie Ibrahim,; Nurzetty Sofia Zainuddin,; Juliana Shamsudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Body mass index (BMI) was one of the reasons people used weight loss products to lose weight. The purpose of this study is to look into the use of weight loss products and their relationship to BMI and associated factors. A cross-sectional study with convenient sampling was conducted on 133 students from Universiti Sains Malaysia, Kubang Kerian (USMKK) Health Campus. Participants were asked to complete an online questionnaire that included sociodemographic information, self-reported weight and height for BMI, weight loss product use, weight loss product usage characteristics, body weight perception and satisfaction, and weight loss product perception. The majority of participants were female (78.2%), 80.5% were Malay, and the mean age was 22 ± 3.1 years old. Majority had a normal BMI (56.4%), whereas 16.5% were underweight, 18.8% were overweight, and 8.3% were obese. Nevertheless, only 10.5% of participants utilised weight loss products. It was discovered that the use of weight loss products is statistically associated with BMI, with a high proportion of users having an overweight or obese BMI (p=0.042). Those who reported using a weight loss product had a higher BMI [25.56 (IQR 6.6) kg/m2 ] than those who did not [21.35 (IQR 5.3) kg/m2 ] (p = 0.015). The use of weight loss products was also statistically associated with perceived product safety (p=0.041) and body weight dissatisfaction (p=0.011). Universities should therefore provide students with appropriate weight loss advice, up-to date information on the safety and efficacy of various weight loss products, and opportunities to enhance their knowledge, self-efficacy, and social support. For future research, it is suggested to wider the research population to overweight and obese adults in Kelantan.